Influencer Marketing and Customers’ Purchase Intention in South Western Nigeria - Oyewumi, Oyewusi Oluwaseun (AGUSPATI Research Institute, 2026)
This study evaluated traits of an influencer that impact customers’ purchase intention. It also examined the effect of influencer marketing on customers’ purchase intention in the southwestern region of Nigeria. These were with a view to investigating the significance of influencer marketing on customers’ purchase intention. The study adopted descriptive survey research design. Primary data were sourced for the study through the use of questionnaire. The population for the study comprised 11,410,324 as indicated on Instagram Social Media Platform spread across the six southwestern states of Nigeria. Using Yamane formula, a sample size of 400 customers was proportionately sourced for this study. Purposive sampling technique was used to select customers who made use of influencers on the Instagram social media platform. This was because the Instagram had the highest number of influencers. Market influencers were captured as presented on the Instagram platform while data on customers’ purchase intention was measured on a 5-point Likert Scale using source attractiveness, integrity and product match up. Data collected were analysed using appropriate statistical analysis. The results showed that the important features/traits of an influencer which impact customers’ purchase intention are influencer’s credibility (t = 5.629; p < 0.05), quality of information (t = 4.534; p < 0.05), and customers’ involvement (t = 5.426; p < 0.05). Furthermore, the results showed a significantly positive relationship between influencer marketing and customers’ purchase intention Influencer credibility (t=19.267, p< 0.05), Quality of Information (t=17.667, p< 0.05) and Customers’ involvement (t=22.818, p< 0.05). The study concluded that influencer marketing has a positive and significant effect on customers’ purchase intention in Southwestern Nigeria.